Alum, Ground Bones and Pebbles: Reader Resistance in The English Broadside - Porter, Gerard (FOCUS: Papers in English Literary and Cultural Studies, 2024)
The known market for London broadsides in the seventeenth century was upwards of twenty thousand, according to Raymond Williams (Long Revolution 182). Moreover, many of these buyers were drawn precisely from those groups that are known to have been active transmitters of occupational songs. Many broadside printers were established in London, and increasingly elsewhere, with the specific intention of serving the new audience of skilled workers, as suggested by the occupations mentioned in the song titles: “The Collier Lad’s Lament,” “The LoveSick Serving Man,” “The London Prentice” and so on. According to Dave Harker, broadsides became the predominant literary form current amongst working people, above all in the towns, in pre-industrial times (193). Through them, a particular song could be disseminated through an area, and a social spectrum, much wider than that covered by an individual performer.